Res iudicata in the canonical penal process in via iudicialis - Borek, Dariusz (Prawo Kanoniczne, 2023)
There is debate in doctrine as to whether judgments in criminal cases become res iudicata or not, as there are different opinions among canonists commenting on this issue and in the rulings of the Roman Rota. As can be seen from the provision found in can. 1643, cases concerning the status of persons, including cases of separation of spouses, never acquire the force of res iudicata. The fundamental question that must be answered in order to resolve this issue is whether judgments in criminal cases belong to matters concerning status personarum or not. When analysing issues related to the possible acquisition of res judicata in criminal cases, it is therefore necessary to take into account not only the provisions specific to criminal proceedings in via iudicialis, but also the provisions of procedural law relating to the institution of res judicata. Criminal proceedings in court have their own norms resulting from the specific nature of such proceedings, but, in accordance with can. 1728, these norms are to be supplemented – nisi rei natura obstet – by the norms provided for proceedings in general and for ordinary contentious proceedings. In criminal proceedings, in accordance with the provisions of can. 1728 § 1, special provisions on matters concerning the public good are also to be applied. In view of the above, canonical criminal proceedings are not really autonomous, since in reality there is one administrative procedure and one ordinary contentious process with certain specifications for cases concerning the imposition and declaration of ecclesiastical penalties. The following issues will be analysed below: selected issues in the field of canonical criminal proceedings in court; fundamental issues related to res judicata; criminal cases and status personarum.